(untitled) (Research, Society and Development, 2022)
Introduction: sleep disorders can greatly impact the quality of life, since sleep has important biological functions such as memory consolidation, binocular vision, thermoregulation, energy conservation and restoration, and restoration of brain energy metabolism. Objective: to review the specialized literature on the characteristics of the most frequent sleep disorders in the general population and their implications for the behavior, daily routine and quality of life of people with this condition. Methodology: this is a study of Systematic Literature Review in which data was collected from a search in the Scielo, Google Academico and VHL databases. Results and discussion: the results indicate that the range of factors associated with sleep disorders may vary according to the population studied. It is necessary to know each reality, as well as the evaluation of the pathologies related to ST, so that a correct treatment can be made, capable of restoring quality of life to people diagnosed with ST. Conclusion: the main point is to know that different populations are associated with different factors that cause sleep disturbance, and knowing these factors is essential to improve the quality of sleep and life and also to know how to treat them correctly.